A Precedência do custeio na implementação de políticas públicas sob a tutela dos direitos fundamentais do cidadão. - Mello, Marcilio Barenco Corrêa de (2013)
This academic paper discusses the sources of funding of general public policies with respect to fundamental rights of the citizen. The exegesis of the relationship contractualist state versus individual seeks to demonstrate why and when, the individual gave up part of his personal liberty, his property, to his detriment and in favor of the State and also the conditions under which historical- developed the preterit social power relations, in particular, the power to tax. This understanding helps us establish the evolution of own tax law itself, which resembles the transition state of the natural liberties arbitrary impositions, followed by the consent of the individual and his group, eventually emptying into the rule of law, today added the values of justice and security to the fullness of its realization. The activity-through the state – revenue collection - became the engine cool exaction on equity and income of the individual, to meet its own operation and the implementation of public policies necessary to achieve the ideals of the welfare state: the welfare of the community. However, it should be emphasized that to achieve reasonable levels in the general allotments carved into the Magna Carta of 1988, the state entity must enforce mechanisms for social justice, gradually reducing social inequalities, for only after, effective public policies, achieve concreteness benefits indispensable to the existential minimum of their fellow citizens. Legal certainty and equality are non-derogable assumptions respecting the fundamental rights of taxpayers, since the sphere of foreign assets (particular) is that you play as precedence source of revenue and provision of funding and training geared to the capitalization of assets of entities that make up the federation. The excessive tax burden should be gradually unencumbered, enabling, pari passu, which the state entity desoneres of welfare policies and support, it only becomes applicable, before a reasonable self-sufficiency of individuals and the collective that belong, thus aiming at the construction of a state Social and Fiscal fully supportable. To do this, avoidance of malpractice of public money is imperative, with significant fighting corruption and should be chosen as priorities strands of various forms of political control, social and institutional available. Finally, without neglecting the discretion essential to managing public administration, the governor should suffer the permanent supervision of their actions and spending practiced, so that we carefully observe strict compliance with the priorities that lead to the effectiveness of full-political foundations constitutional erected in our nation.